2015
DOI: 10.1186/s13039-015-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Rare double-hit with two translocations involving IGH both, with BCL2 and BCL3, in a monoclonal B-cell lymphoma/leukemia

Abstract: BackgroundChronic Lymphocytic Leukemia (CLL) is a lymphoproliferative disease characterized by multiple recurring clonal cytogenetic anomalies and is the most common leukemia in adults. Chromosomal abnormalities associated with CLL include trisomy 12 and IGH;BCL3 rearrangement [t(14;19)(q32;q13)] that juxtaposes a proto-oncogenic gene BCL3 and an immunoglobulin heavy chain, a translocation that may be associated with shorter survival. In addition to the IGH;BCL3 rearrangement, other translocations involving 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…BCL2 rearrangements characteristically observed in follicular lymphoma have been uncommonly reported in CLL/SLL [9,10,11,12]. More unusual are cases of CLL/SLL with double-hit translocations involving BCL2 and IG loci.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…BCL2 rearrangements characteristically observed in follicular lymphoma have been uncommonly reported in CLL/SLL [9,10,11,12]. More unusual are cases of CLL/SLL with double-hit translocations involving BCL2 and IG loci.…”
Section: Figmentioning
confidence: 99%
“…More unusual are cases of CLL/SLL with double-hit translocations involving BCL2 and IG loci. Lau et al [11] reported a case of CLL with trisomy 12, t(14;18) ( IGH-BCL2 ), and t(8;14) (IGH-MYC) within the same clone, while Alpatov et al [9] reported a case of CLL with trisomy 12, t(14;18), and t(14;19) ( IGH-BCL3 ) within the same clone. In addition, 2 case series of CLL/SLL, harboring t(14;18) translocations also revealed trisomy 12 in approximately 13/22 (59%) and 6/12 (50%) cases, which is higher than the reported 15-20% observed in common CLL/SLL [4,10,12].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 8 10 ] The most frequent translocation in CLL is t(14;19) (q32;q13), which juxtaposes IGH and BCL3 resulting in overexpression of BCL3 [ 11 ] and is usually associated with unfavorable clinical outcome and trisomy 12. [ 8 , 12 ] It was proposed that these 2 changes might cooperate for malignant transformation. [ 13 ] In contrast, patients with del(13q) have a better survival than the patients with other cytogenetic abnormalities.…”
Section: Introductionmentioning
confidence: 99%